Tourism 4.0: digital media communication on online impulse buying and e-satisfaction - Bethani Suryawardani; Astri Wulandari; Dandy Marcelino (BISMA (Bisnis dan Manajemen), 2021)
The rapid development of ICT changes communication practices and strategies involving government and stakeholder policies in the tourism industry. This is also a challenge and an opportunity for every country in general and tourist destinations to create interesting information on websites and other online media as a promotion. This study aims to find out how digital communication media, especially websites, can influence impulsive buying online and e-satisfaction. The quantitative research approach used surveys of 400 respondents. Data analysed using the Structural Equation Modelling (SEM) technique. The study found that website quality, website personality, and sales promotion influence the impulsive online purchases. Furthermore, website quality, website personality, and impulsive online buying have a simultaneous effect on e-satisfaction. Online travel agents are advised to pay more attention and improve website quality, website personality, and online impulsive buying as the predictor of e-satisfaction.